THE EFFECT GOVERNMENT REGULATIONS, CORPORATE CHARACTERISTICS, EARNING MANAGEMENT ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Reyhan Mahardika; Puji Handayati (ID Solutions, 2022)
The purpose of this research is to determine the effect of government regulations, corporate characteristics and earnings management on the disclosure of corporate social responsibility. This research was conducted on mining sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique was carried out by purposive sampling method of 40 respondents. In this research, documentation technique becomes a method of collecting data by looking at the company's annual report. The analysis in this research uses multiple linear regression. With the result that government regulation, profitability, leverage and firm size do not affect the disclosure of corporate social responsibility. Meanwhile, earnings management affects CSR disclosure in mining companies in 2015-2019.